Self-efficacy and its relation to academic performance in students of mathematics education - Zamora-Araya, José Andrey; Cruz-Quesada, Jesús Daniel; Amador-Montes, Marlon Steven (Innovaciones Educativas, 2020)
In the field of educational research, the construct of self-efficacy, framed within cognitive social theory, has been studied to respond to low academic performance. For this reason, the research aims to analyze how the sources of mathematical self-efficacy are related to academic performance in mathematics (APM or RAM-acronym in Spanish), in students of the Bachelor’s and Licentiate degrees in Teaching Mathematics (BLEM-acronym in Spanish) of the National University, Costa Rica (UNA). 92 students of I, II and III levels of the BLEM majors participated and the scale of sources of mathematical self-efficacy (EFAM-acronym in Spanish), adapted to Spanish by Zalazar, Aparicio, Ramírez and Garrido (2011), was applied to them. The study is correlational and the multiple regression technique was used to determine the correlation between APM and the sources of the construct, using as covariates, sex, scholarship tenure, parents’ educational level, career choice, career level and the fact of having failed. The results show the relevance of direct experience (p <0.050) as a predictor of RAM; as well as the fact of having failed (p <0.001). The other variables are of practical importance, except for verbal persuasion. In short, the importance of mathematical self-efficacy in the APM is reaffirmed.